Regional governance as a success factor in protected area management. Network analysis of the Lüneburg Heath Nature Park (Germany) - Ströbel, Kerstin; Job, Hubert; von Ruschkowski, Eick (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Protected areas are crucial for landscape-scale conservation, but striking a balance between centralised guidance (heteronomy) and local autonomy (self-determination) is essential. This balance is particularly important for parks that cross administrative boundaries or impose land-use restrictions, as these factors can impact local acceptance and actors’ responsibilities. Analysing governance structures can unveil communication effectiveness, power distribution and collaboration levels within protected areas. This paper presents a network analysis intended to obtain empirical evidence of the above. To the best of our knowledge, this is the first such analysis to be conducted in a German conservation context. This approach reveals responsibility distributions and motives behind spatial interventions. In the pilot study of the Lüneburg Heath Nature Park, 34 actors were identified. In the core group, data was generated from 12 semi-structured expert interviews. We identified existing communicative and collaborative structures between key actors, local rights holders and stakeholders facing implementation challenges. Leveraging structures like the ‘Nature Conservation Coordination Group’, which has the status of a higher-level assembly, can encourage an open communication culture and affirm each actor’s value. We conclude that strengthening existing governance structures and implementing them on the ground, even on an informal basis, is essential for fostering a shared understanding and greater acceptance of landscape-scale conservation issues.
Keywords: Protected areas; Landscape-scale conservation; Lüneburg Heath; Nature park; network analysis; Regional governance